2001
DOI: 10.1021/tx000208y
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationships for a Large Diverse Set of Natural, Synthetic, and Environmental Estrogens

Abstract: Understanding structural requirements for a chemical to exhibit estrogen receptor (ER) binding has been important in various fields. This knowledge has been directly and indirectly applied to design drugs for human estrogen replacement therapy, and to identify estrogenic endocrine disruptors. This paper reports structure-activity relationships (SARs) based on a total of 230 chemicals, including both natural and xenoestrogens. Activities were generated using a validated ER competitive binding assay, which cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
357
1
7

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(388 citation statements)
references
References 52 publications
17
357
1
7
Order By: Relevance
“…In a similar way, Chalopin et al (2010) showed that the endothelium-dependent vasorelaxation of delphinidin and a red wine extract is mediated via ERa. With respect to ERa, the presence of up to 2-OH groups in the B-ring of the molecular structure decreased the affinity of the anthocyanins to the ERa (Fang et al 2001). In contrast, delphinidin-3-glucoside and gallic acid with 3-OH groups demonstrated the highest affinity for ERb in our study.…”
Section: Relative Affinity For Era and Erbcontrasting
confidence: 59%
“…In a similar way, Chalopin et al (2010) showed that the endothelium-dependent vasorelaxation of delphinidin and a red wine extract is mediated via ERa. With respect to ERa, the presence of up to 2-OH groups in the B-ring of the molecular structure decreased the affinity of the anthocyanins to the ERa (Fang et al 2001). In contrast, delphinidin-3-glucoside and gallic acid with 3-OH groups demonstrated the highest affinity for ERb in our study.…”
Section: Relative Affinity For Era and Erbcontrasting
confidence: 59%
“…A wide variety of pharmacologically relevant functions is assigned to these compounds [22], from antibacterial, antifungal, antiviral, anti-spasmolytic, estrogen-like, anti-inflammatory and anti-HIV to anticancer [23][24][25][26][27][28][29][30][31]. This group of compounds contains a common moiety -a chromone skeleton with a phenyl substituent in the pyrone ring ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative structure-activity relationship (QSAR) models and qualitative SAR approaches have had some success in identifying and depicting structural features that contribute to the ability of a chemical to interact with steroid hormones, for both the estrogen receptor (ER) (Anstead et al 1997;Fang et al 2001;McKinney and Waller 1994;Tong et al 1997aTong et al , 1997bTong et al , 1998Waller et al 1996b;Wiese and Brooks 1994) and the AR (Loughney and Schwender 1992;Mekenyan et al 1997;Singh et al 2000;Tucker et al 1988;Waller et al 1996a). In the case of environmentally occurring chemicals, studies have revealed a common pattern of steric and electronic features involved in molecular recognition and receptor binding affinity, in spite of the molecular diversity of such data sets.…”
mentioning
confidence: 99%